The Effect of Ownership Structure on the Going Concern Companies Listed in the Iraqi Stock Exchange - Ali Mohammed Ridha Al-Kamoosy , Alward; Ahmed Mohammed Al-Ani , Safaa (Journal of Economics and Administrative Sciences, 2024)
The ability of the economic unit to continue is one of the basic assumptions for preparing financial statements. Therefore, users of these statements need to have a clear image of the unit’s performance and financial situation and to ensure that there is no indicator warning of financial distress. For example, there is a conflict of interest between the unit’s shareholders on the one hand and the management on the other hand. Therefore, this research seeks to study the effect of the difference in the nature of the ownership structure on the going concern of economic units. The research is based on the hypothesis that each type of ownership structure has a negative impact on the going concern unit. The research selected five economic units listed on the Iraqi Stock Exchange from the service sector as a sample for the research. Data is collected for the period extending from 2011-2021. The research used the survey method to measure the ownership structure and applied a Kida Model to measure going concern. The most significant results of the research are a negative effect of institutional ownership, concentrated ownership, and management ownership on the going concern of the unit, In contrast, the effect is positive for both government ownership and family ownership, and foreign ownership has no effect.Paper type: Research paper